Aluminium(I) anion-supported zero-valent palladium complexes - Yan, Chenting (2024)
Monovalent group 13 element anions, such as boryl [BR2]− and aluminyl [AlR2]− anions, serve as nucleophiles to form diverse group 13 element-containing molecules. Although transition-metal complexes bearing group 13 ligands are accessible via salt metathesis with these anions, zero-valent transition-metal complexes have never been reported. In the present study, the synthesis, isolation and characterization of palladium complexes in the zero-oxidation state featuring one, two and three anionic aluminium ligands are reported. The Pd(0) complexes result from the ligand exchange reaction between bis(tri-tert-butylphosphoranyl)palladium and cyclic (alkyl)(amino)aluminium (CAAAl) anions. X-ray crystallographic and spectroscopic analyses, with the aid of quantum chemical calculations, disclose the highly negatively charged Pd centre, polarized Pd(δ−)–Al(δ+) covalent bond, as well as the pronounced σ-donor and π-acceptor properties of the CAAAl ligand. Remarkably, 3K[Pd(0)(CAAAl)3] readily reacts with bis(pinacolato)diboron, leading to a bis(boryl)bis(aluminyl)Pd(II) complex via an unprecedented oxidative addition of the B–B bond to the Pd centre. (Figure presented.)